Best Answer

move the -10 onto the other side and swap the sign

x=3+10

x=13

*****************

My version is basically the same as above, but...

x-10=3

First you would add 10 to both sides. This balances out the fact that in the equation you are subtracting. It the equation was x+10 you would subtract 10. Add.

x-10=3

+10 +10

x=13

So your answer is that X is 13.

Q: How do you do x-10 equals 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

45.7*10-3 = 0.0457

0.006533 = 6.533e-3 or 6.533 x10^-3

0.00604

9.0 x10^-3

The new mean would be 7. The mean is the average of the data. (x1+x2+x3+x4+x5+x6+x7+x8+x9+x10)/10=21 [(x1/3)+(x2/3)+(x3/3)+(x4/3)+(x5/3)+(x6/3)+(x7/3)+(x8/3)+(x9/3)+(x10/3)]/10=? [(1/3)(x1+x2+x3+x4+x5+x6+x7+x8+x9+x10)]/10=? [(x1+x2+x3+x4+x5+x6+x7+x8+x9+x10)/10]/3= 21/3=7

Related questions

3 x10 30 x10

No, since there's no decimal point, it equals 875 or 8.75 x 10^2

It looks like an incomplete equation.

Yes, if x10=y.

1.357 x10-3 in standard notation is: 0.001357

e could either mean x10^ or 2.718. I think in this case it means x10^. THIS ANSWER WILL REQUIRE AN UPDATE.

29000000

kg x10^3

45.7*10-3 = 0.0457

2.058911321...x10^14

0x10=10 because your counting 10 0 times

0.006533 = 6.533e-3 or 6.533 x10^-3